Hepatitis C Virus core protein inhibits tumor suppressor protein promyelocytic leukemia function in human hepatoma cells - Herzer, Kerstin; Krammer, Peter H.; Hofmann, Thomas G. (Cancer research, 2005)
Tumor suppressor protein promyelocytic leukemia (PML) is implicated in apoptosis regulation and antiviral response. PML localizes predominantly to PML-nuclear bodies (PML-NB), nuclear macromolecular complexes regulating tumor suppressor protein p53 activity. Consistent with the function of PML in the cellular antiviral response, PML-NBs represent preferential targets in viral infections. In the case of hepatitis C virus (HCV) infection, important characteristics are nonresponsiveness to IFN therapy and development of hepatocellular carcinoma. However, the mechanisms which lead to the development of hepatocellular carcinoma are largely unknown. Here, we show that HCV core protein localizes to the cell nucleus in PML-NBs, where it colocalizes with p53. The HCV core interacts with endogenously expressed PML isoform IV (PML-IV), a key regulator of p53 activity. Importantly, we show that HCV core protein inhibits PML-IV-induced apoptosis and interferes with the coactivator function of PML-IV for proapoptotic p53 target genes including CD95 (Fas/APO-1). In particular, we found that the HCV core inhibits p53-mediated target gene expression by predominantly targeting the coactivator function of PML-IV because HCV core-mediated p53 target gene repression was absent in PML-ablated cells. HCV core expression abrogated both p53 serine 15 phosphorylation and lysine 382 acetylation, two p53-activating posttranslational modifications which were previously linked to an increased PML-NB formation. Taken together, our results suggest a potential mechanism for HCV-associated development of hepatocellular carcinoma through HCV core-mediated inactivation of the PML tumor suppressor pathway.